Os efeitos do estresse crônico no desenvolvimento da depressão - Petrilli, Rafaela Abdelnur (Universidade Federal de São Carlos, 2024)
Depression, particularly Major Depressive Disorder (MDD), is a heterogeneous and debilitating neuropsychological disorder that affects approximately 280 million people worldwide. Its main symptoms include a depressed mood and a decrease in interest or loss of pleasure in all activities. Stress is considered a physiological response of the body to situations of change or threat. Chronic stress, this is, long-term stress, in turn, causes a permanent state of arousal and leads to significant changes in brain function, making the human brain more vulnerable to the development of depression. The present study aimed to review national and international literature from 2018 to 2023 on the effects of chronic stress on the development of depression. Articles written in English, Portuguese, and Spanish were considered eligible if they focused on the causal relationship between chronic stress and depression. The articles were consulted in the following databases: National Center for Biotechnology Information (NCBI/PubMed), Scientific Electronic Library Online (SciELO), PsycINFO, and Latin American and Caribbean Health Sciences Literature (LILACS). The analysis of the 24 selected articles revealed that prolonged exposure to stress resulted in the development of depressive-like symptoms
The effects of chronic stress on the development of depression
Keywords: Estresse; Stress; Estresse crônico; Chronic stress; Depressão; Depression; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA